Late Quaternary Montane Forest Dynamics From Equatorial East Africa: A Biome Perspective - Esther N. Githumbi; Jemma Finch; Rahab N. Kinyanjui; Colin Courtney‐Mustaphi; Paul Musili; Stephen Rucina; Julius Lejju; Peter Liljenberg; Rob Marchant (Journal of Biogeography, 2025)
Aim Understanding environmental change over large spatial and temporal scales requires working at a broad ecological scale to enable cross‐site comparisons. This allows data‐based comparisons to dynamic vegetation model outputs, with utility for climate and land cover modelling. We synthesise multisite pollen data at the biome level to understand Equatorial Afromontane ecosystem response to climate change over the last 50,000 years and quantitatively document the timing, character and spatial patterns of ecosystem transitions. Location Mountains of Equatorial East Africa. Time Period Late Quaternary (50,000 cal year BP–present). Taxon Angiosperms (trees, shrubs and grasses), gymnosperms (conifers), pteridophytes (ferns) and bryophytes (clubmosses). Methods A literature review revealed 58 available published pollen sites from Equatorial East African Mountains. Original geochronological and palynological data were collated from 34 sites from the African Pollen Database (APD) and directly from authors. Pollen taxonomies were updated and harmonised using the African Plant Database. The geochronologies were reanalysed and radiocarbon data ( n = 219) were IntCal20 calibrated to develop linearly interpolated age‐depth models. The 636 pollen taxa were grouped into 21 plant functional types and combined into seven biomes that represent the range of montane ecosystems. A rate of change analysis at each site provided a scale of the change through time at each site. Results Mesic montane forest biomes were present throughout the 50,000 cal year BP. Cold and dry montane biomes expanded during and after the Last Glacial Maximum (LGM). Warm and wet forest biomes expanded from the early Holocene and more open biomes expanded in the Late Holocene. Regional differences were observed, such as the Eastern Arc Mountain sites recording relatively little change in comparison with isolated volcanic mountains. The rate of change analysis highlights periods with a high rate of change (45,000–35,000, 11,000–5000 and 5000–present) while 35,000–20,000 is relatively stable. Main Conclusions Equatorial East African Montane forests are driven by local to regional vegetation responses to past climate changes. The research highlights that both the pace and nature of interactions in ecological systems vary widely across these montane forests.

Farmland biodiversity and agricultural management on 237 farms in 13 European and two African regions - Gisela Lüscher; Youssef Ammari; Aljona Andriets; Siyka Angelova; Michaela Arndorfer; Debra Bailey; Katalin Balázs; Marion Bogers; Robert G. H. Bunce; Jean‐Philippe Choisis; Peter Dennis; Mario Díaz; et al. (Ecology, 2016)
Farmland is a major land cover type in Europe and Africa and provides habitat for numerous species. The severe decline in farmland biodiversity of the last decades has been attributed to changes in farming practices, and organic and low‐input farming are assumed to mitigate detrimental effects of agricultural intensification on biodiversity. Since the farm enterprise is the primary unit of agricultural decision making, management‐related effects at the field scale need to be assessed at the farm level. Therefore, in this study, data were collected on habitat characteristics, vascular plant, earthworm, spider, and bee communities and on the corresponding agricultural management in 237 farms in 13 European and two African regions. In 15 environmental and agricultural homogeneous regions, 6–20 farms with the same farm type (e.g., arable crops, grassland, or specific permanent crops) were selected. If available, an equal number of organic and non‐organic farms were randomly selected. Alternatively, farms were sampled along a gradient of management intensity. For all selected farms, the entire farmed area was mapped, which resulted in total in the mapping of 11 338 units attributed to 194 standardized habitat types, provided together with additional descriptors. On each farm, one site per available habitat type was randomly selected for species diversity investigations. Species were sampled on 2115 sites and identified to the species level by expert taxonomists. Species lists and abundance estimates are provided for each site and sampling date (one date for plants and earthworms, three dates for spiders and bees). In addition, farmers provided information about their management practices in face‐to‐face interviews following a standardized questionnaire. Farm management indicators for each farm are available (e.g., nitrogen input, pesticide applications, or energy input). Analyses revealed a positive effect of unproductive areas and a negative effect of intensive management on biodiversity. Communities of the four taxonomic groups strongly differed in their response to habitat characteristics, agricultural management, and regional circumstances. The data has potential for further insights into interactions of farmland biodiversity and agricultural management at site, farm, and regional scale.

Tracing long‐term tropical montane ecosystem change in the Eastern Arc Mountains of Tanzania - JEMMA FINCH; MATTHEW WOOLLER; ROB MARCHANT (Journal of Quaternary Science, 2014)
Pollen, charcoal, stable carbon and nitrogen isotope, and radiocarbon analyses are used to reconstruct a palaeoenvironmental record from the Eastern Arc Mountains (EAM), Tanzania, dating back >45 000 years. A sedimentary hiatus covering the last glacial‐interglacial transition (LGIT) and early to mid Holocene follows the lead up to the Last Glacial Maximum (LGM) period. A late Holocene portion of the record is included as a modern analogue. Before 45 000 cal a BP, very low regional pollen counts imply open vegetation surrounding the site. Subsequently, the development of extensive montane forest characterizes a relatively mesic pre‐LGM. The transition into the LGM witnessed a marked shift from C 3 ‐ to C 4 ‐dominated biomass, representing an expansion of open forest dominated by grasses. These changes may be attributed to a combination of enhanced moisture stress and CO 2 limitation, factors that may have been exacerbated by an intensive fire regime, as evident from the charcoal record. This is supported by a decrease in montane forest taxa, coupled with an associated expansion of C 4 graminoids and ericaceous heathland to form a montane grassland mosaic similar to that previously recorded on other East African mountains around the time of the LGM but not, to date, having been shown in the Eastern Arc Mountains.

A palaeoecological investigation into the role of fire and human activity in the development of montane grasslands in East Africa - Jemma Finch; Rob Marchant (Vegetation History and Archaeobotany, 2011)

A636P testing in Ashkenazi Jews - G. guillem Jose; G. moore Harvey; Palmer Crystal; Glogowski Emily; Rob Finch; Nafa Khedoudja; J. Markowitz Arnold; Offit Kenneth; A. Ellis Nathan (Familial Cancer, 2004)